Incidence and management of cerebrospinal fluid fistulas in 336 multilevel laminectomies with noninstrumented fusions - Epstein, Nancy E. (Surg Neurol Int, 2015)
BACKGROUND: The incidence (e.g., 3–27%) and the types of cerebrospinal fluid (CSF) fistulas occurring during multilevel lumbar laminectomy with noninstrumented spinal fusions varies. METHODS: From 2000 to 2015, we retrospectively evaluated the incidence/etiologies of CSF fistulas occurring for 336 patients undergoing average 4.7 laminectomies with average 1.4 level noninstrumented fusions over a 15 year period. The varied etiologies of CSF leaks included; ossification of the yellow ligament (OYL) extending through the dura, postoperative surgical scar, iatrogenic traumatic leak, epidural steroid injections (ESI), resection of synovial cysts, and the removal of intradural tumors. Techniques for primary repairs included combinations of; 7-0 Gore-Tex (Newark, Delaware, USA) sutures, micro-dural staples, muscle patch/other (e.g., bovine pericardial) grafts, fibrin sealants/glues (e.g., Tisseel; Baxter International Inc., Westlake Village, CA, USA), and Duragen (Integra LifeSciences, Hawthorne, NY, USA) including both the thin and suturable types. RESULTS: The etiologies of CSF fistulas in descending order included: Epidural spinal injections (ESI) (7 patients), synovial cysts (6 patients), OYL (5 patients), and equally for postoperative scar and intradural tumors (3 patients). CSF fistulas occurred in 24 (7.14%) of 336 patients; this frequency was reduced to 4.2% when ESI and intradural tumors were excluded. CONCLUSION: CSF fistulas occurred in 7.14% of 336 patients undergoing average 4.7 multilevel laminectomies with average 1.4 level noninstrumented fusions attributed to a lumbar stenosis with mild/moderate instability. The dural repair addressed seven prior ESI, six synovial cysts, five OYL, and operative scarring and intradural tumors (three apiece). Knowing the pathologies contributing to CSF fistulas should help the surgeon to better anticipate and treat these fistulas.